1971
DOI: 10.2136/sssaj1971.03615995003500020027x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Straw Decomposition in the Field

Abstract: Wheat (Triticum aestivum) varieties ‘Nugaines’ and ‘Lemhi’ were grown on Portneuf silt loam soil with three nitrogen and three irrigation treatments in 1967. After harvest, 84 kg N/ha was applied to half of each plot before plowing. Uniform straw samples were enclosed in fiberglass cloth bags and buried in the plots September 7. The straw placed in N‐treated plots received sufficient N in solution to increase the straw N from about 0.29 to 1.5%. Straw samples were recovered November 15, after the soil had cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
10

Year Published

1977
1977
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 8 publications
1
24
0
10
Order By: Relevance
“…Como a palhada de cana-de-açúcar apresenta, em média, uma relação C:N de aproximadamente 100, é de se esperar grande imobilização do N do solo, uma vez que, como regra geral, para relações C:N maiores que 15 a 20, ocorre imobilização (Smith & Douglas, 1971;Siqueira & Franco, 1988).…”
Section: Introductionunclassified
“…Como a palhada de cana-de-açúcar apresenta, em média, uma relação C:N de aproximadamente 100, é de se esperar grande imobilização do N do solo, uma vez que, como regra geral, para relações C:N maiores que 15 a 20, ocorre imobilização (Smith & Douglas, 1971;Siqueira & Franco, 1988).…”
Section: Introductionunclassified
“…2). SMITH and DOUGLAS (5) reported that loss in weight of wheat straw in the field was larger at the early stage but smaller at the later stage when fertilizer was added than when it was not. Kuo and BARTHOLOMEW (3) reported that the addition of inorganic nitrogen (ammonium sulfate and urea) to corn stalks both accelerated and retarded decomposition-large additions of inorganic nitrogen retarded loss in weight of corn stalks.…”
Section: Resultsmentioning
confidence: 99%
“…A decomposição dos resíduos culturais depende da natureza e da quantidade do material vegetal (Brown & Dickey, 1970;Bertol et al, 1998;Gilmour et al, 1998), da fertilidade do solo (Smith & Douglas, 1968, 1971, do manejo da cobertura e do grau de fracionamento do resíduo (House & Stinner, 1987), além de condições climáticas (Lyon, 1998;Gilmour et al, 1998), representadas principalmente pelo regime de chuvas e pela temperatura, que influem na atividade microbiana do solo.…”
Section: Introductionunclassified
“…A velocidade de decomposição, segundo Smith & Douglas (1968;1971), não é influenciada, por outro lado, pela quantidade de N mineral do solo.…”
Section: Introductionunclassified